Basophils inhibit proliferation of CD4+ T cells in autologous and allogeneic mixed lymphocyte reactions and limit disease activity in a murine model of graft versus host disease. Issue 2 (June 2015) - Hermann, Fabian J.; Rodriguez Gomez, Manuel; Doser, Kristina; Edinger, Matthias; Hoffmann, Petra; Schiechl, Gabriela; Talke, Yvonne; Göbel, Nicole; Schmidbauer, Kathrin; Syed, Shahzad N.; Brühl, Hilke; Mack, Matthias
Summary Basophils are known to modulate the phenotype of CD4+ T cells and to enhance T helper type 2 responses in vitro and in vivo. In this study, we demonstrate that murine basophils inhibit proliferation of CD4+ T cells in autologous and allogeneic mixed lymphocyte reactions. The inhibition is independent of Fas and MHC class II, but dependent on activation of basophils with subsequent release of interleukin‐4 (IL‐4) and IL‐6. The inhibitory effect of basophils on T‐cell proliferation can be blocked with antibodies against IL‐4 and IL‐6 and is absent in IL‐4/IL‐6 double‐deficient mice. In addition, we show that basophils and IL‐4 have beneficial effects on disease activity in a murine model of acute graft‐versus‐host disease (GvHD). When basophils were depleted with the antibody MAR‐1 before induction of GvHD, weight loss, GvHD score, mortality and plasma tumour necrosis factor levels were increased while injection of IL‐4 improved GvHD. Basophil‐depleted mice with GvHD also have increased numbers of CD4+ T cells in the mesenteric lymph nodes. Our data show for the first time that basophils suppress autologous and allogeneic CD4+ T‐cell proliferation in an IL‐4‐dependent manner.